MANAGEMENT AND MATERNAL OUTCOME IN MORBIDLY ADHERENT PLACENTA - Sultana, Nighat; Mohyuddin, Sobia; Jabbar, Tahira (Journal of Ayub Medical College Abbottabad, 2011)
Background: Morbidly adherent placenta (MAP) with its variants is one of the most feared complications causing high morbidity and mortality in obstetrics. The objective of this study was to analyse different management options and maternal outcome in diagnosed cases of morbidly adherent placenta. Methods: Descriptive case series was carried out in Obstetrics and Gynaecology Department, Combined Military Hospital, Rawalpindi and one private hospital from Jan 2008 to Dec 2010. During this period all cases of morbidly adherent placenta diagnosed by colour flow Doppler and MRI were analysed. Operative delivery was carried out in all patients. Three different surgical managements namely total abdominal hysterectomy with non separation of placenta, subtotal hysterectomy and trial haemostasis with uterine sparing surgery were carried out on when and where required basis. The outcome like total blood loss, blood transfused, Intensive unit care, postnatal complications including febrile morbidity, hospital stay and prolonged follow ups, were recorded. Results: Total 32 cases of morbidly adherent placenta diagnosed by colour Doppler ultrasound/MRI (magnetic resonance imaging) were identified. In this study the frequency of morbidly adherent placenta found to be 1/274.8 deliveries and 1/122.6 caesarean sections. Initially total caesarean hysterectomy was performed in 16 patients, while subtotal hysterectomy in 9 and Trial haemostasis with uterine sparing in 7 cases out of which two cases underwent total hysterectomy due to massive postpartum haemorrhage same day. One case in subtotal hysterectomy for placenta percreta with bladder invasion had re-laparotomy for bladder fistula, while two for severe postpartum haemorrhage. Two needed ventilator support. Maternal morbidity was greater in subtotal hysterectomy and uterine sparing group. One patient died in this study. Conclusion: Antenatal diagnosis of morbidly adherent placenta followed by well-planned total abdominal hysterectomy with non-separation of placenta adapting multidisciplinary approach is the best surgical option to reduce maternal morbidity/mortality. Keywords: morbidly adherent placenta, total abdominal hysterectomy, Trial haemostasis